Tasks in explicit L2 pronunciation instruction: FonF vs. FonFS in improving phonemic accuracy and comprehensibility - Tabandeh, Farhad; Moinzadeh, Ahmad; Barati, Hossein (Penerbit Universiti Kebangsaan Malaysia, 2018)
The effects of focusing second/foreign language (L2) learners’ attentions on phonological forms while communicating in meaningful discourse has recently attracted attention in L2 pronunciation research. One such treatment is focus-on-form (FonF) instruction wherein L2 learners practice and notice pronunciation features in communicative tasks rather than in decontextualized exercises and drills (i.e., focus-on-forms [FonFS]). Given this, the current study investigated the differential effects of FonF and FonFS instructions on improving Iranian English as a foreign language (EFL) learners’ pronunciation of the most problematic English consonants. After identifying the problematic English consonants (i.e., /θ/, /ð/, /w/, /ŋ/) via remedial and expert judgment approaches, 45 pre-intermediate learners embarked on an 8-hour course. The experimental group received FonF, the comparison group received FonFS, and the control group had a free conversation class minus any feedback on the target consonants. Learners’ pronunciations were measured in terms of phonemic accuracy and comprehensibility in controlled and spontaneous tasks. The results of immediate and delayed post-test for phonemic accuracy revealed that whereas both FonF and FonFS were equally effective in controlled tasks, only FonF instruction proved effective up to the delayed post-test in spontaneous tasks; no such improvements, however, were observed for the control group. Results also showed that improvements in phonemic accuracy led to overall comprehensibility enhancements in EFL learners’ speech. The article concludes with some pedagogical implications of the findings.